The digital era. - Chamoux, Jean-Pierre, 1940- (Wiley-ISTE, 2019)
Over 200 years, industry has mastered iron, fire, power and energy. Today, electronics shape our everyday objects with the widespread integration of chips; from computers and telephones to keys, games and white goods. Data, software and computation structure our behavior and the organization of our lives. Everything is translated into data: the digit is king. Consisting of three volumes, The Digital Era explores technical, economic and social phenomena that result from the generalization of the Internet. This second volume discusses the impact of digital technology on the evolution of market relations and the media and examines the reasons why such changes put political economy to the test.